IMPLEMENTASI BLENDED LEARNING DI MASA PANDEMI COVID-19 PADA STIE WIRA BHAKTI MAKASSAR - Indira Basalamah (AkMen JURNAL ILMIAH, 2020)
Productivity asa a result of learning is an achievement to change individual behavior for the better, encourage ego-involment and useful for many people. This is can be achieved if the campus is able to compete and adapt to changes in technology, information and communication.When the Covid-19 Pandemic hit the world, including Indonesia, the education had to change and even modify learning methods to achieve lecture produktivity. Blended Learning as a learning enrichment is considered very effective supported by intristic and extristic motivation, The study aims to identify and analyze the effect of blended learning effectiveness and motivation on the productivity of lecturers and students at STIE Wira Bhakti Makassar. The research sample was 63 lecture of STIE Wira Bhakti Makassar and the analysis method used was multiple regression analysis with the IBM SPSS Statistics program. The results showed that the effectiveness of the blended learning method and motivation had a positive and segnificant effect on the productivity of the lecturers and students of STIE Wira Bhakti Makassar.